Edukasi “Pupuk Kodomo” Limbah Kotoran Domba dengan Media Larva BSF di Bamboe Koening Farm - Budiyati, Eni; Mustofa, Malik; Mulayningtyas, Akida; Pratama, M Rizki Abid; Fatimah, Lutfia Bunga; Puspita Sari, Fera Nur; Chanifah, Amirul; Somantri, Muhammad Aufa Fakhry (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2024)
The community service activity "Pupuk Kodomo" program is carried out to provide a problem solving regarding the processing of livestock manure waste that has not been optimally utilized. In overcoming this problem, Bamboe Koening Farm (as a partner) was educated about processing livestock manure waste using Black Soldier Fly (BSF) larvae as a decomposing agent in bioconversion. The stages of implementation include surveys and partner situation analysis studies, socialization of the "Pupuk Kodomo" program, training and program assistance, education from an economic review and product marketing, periodic monitoring of "Pupuk Kodomo" program activities, and evaluation of implementation results. The results of community service activity changed the habits of sheep goat farmers in the Sukoharjo area to be more innovative, they optimally processed livestock manure waste into a valuable product, namely "Pupuk Kodomo" Maggot media sheep dung fertilizer. The sales of "Pupuk Kodomo" can improve the economy of goat sheep farmers in the Sukoharjo area. In addition, "Pupuk Kodomo" contains phosphorus pentoxide (0.98%) and potassium oxide (1.43%), this shows that the content of "Pupuk Kodomo" is higher than conventional compost fertilizer which contains phosphorus pentoxide (0.69%) and potassium oxide (0.93%) so that "Pupuk Kodomo" can compete in the market.